Dynamics and optimal control of road vehicles - Limebeer, David J. N.; Massaro, Matteo (Associate professor of applied mechanics) (Oxford University Press, 2019)
The broad aim of this text is to provide a comprehensive coverage of the modelling and optimal control of both two- and four-wheeled road vehicles. The first focus of the work is a review of classical mechanics and its use in building vehicle and tyre dynamic models. The second is nonlinear optimal control, which is used to solve a range of minimum-time, minimum-fuel, and track curvature reconstruction problems.